KETAHANAN PANGAN DI KAMPAR KIRI PADA MASA REVOLUSI - Amanan, Amanan; Sabrina, Sabrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study analyzes the dynamics of food security in Kampar Kiri during the Indonesian Revolution, particularly during the Second Dutch Military Aggression (1948–1949). The urgency of this research lies in the lack of studies on food security in the context of the revolution, especially in strategic areas such as Kampar Kiri. This study provides a new perspective on how the local community supported the independence fighters (PDRI) in surviving amidst the war for independence. Using a social history approach, this article explores how the local population managed food resources in times of war and economic instability. An analysis of archival documents, oral sources, and literature studies reveals that Kampar Kiri served as a strategic route for guerrilla forces, directly impacting food production and distribution. The local community developed locally based adaptation strategies to sustain food supplies and support the military struggle.Keywords: Food Security; Social History; Kampar Kiri; Indonesian Revolution